2012
DOI: 10.1038/ncomms1680
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsically labile α-helix abutting the BCL9-binding site of β-catenin is required for its inhibition by carnosic acid

Abstract: Wnt/β-catenin signalling controls development and tissue homeostasis. Moreover, activated β-catenin can be oncogenic and, notably, drives colorectal cancer. Inhibiting oncogenic β-catenin has proven a formidable challenge. Here we design a screen for small-molecule inhibitors of β-catenin's binding to its cofactor BCL9, and discover five related natural compounds, including carnosic acid from rosemary, which attenuates transcriptional β-catenin outputs in colorectal cancer cells. Evidence from NMR and analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 53 publications
6
127
0
Order By: Relevance
“…(B) The biosynthesis of tanshinone and carnosic acid begins with the cyclization of GGPP (12) by a class II diTPS to produce (+) copalyl diphosphate (CPP) (13), which is in turn converted to miltiradiene (14) by a class I diTPS. Spontaneous oxidation of 14 gives rise to abietatriene (15), which is oxidized to ferruginol (16) by a CYP enzyme. However, uncharacterized subsequent events lead to carnosic acid (1) and tanshinones (2-4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(B) The biosynthesis of tanshinone and carnosic acid begins with the cyclization of GGPP (12) by a class II diTPS to produce (+) copalyl diphosphate (CPP) (13), which is in turn converted to miltiradiene (14) by a class I diTPS. Spontaneous oxidation of 14 gives rise to abietatriene (15), which is oxidized to ferruginol (16) by a CYP enzyme. However, uncharacterized subsequent events lead to carnosic acid (1) and tanshinones (2-4).…”
Section: Resultsmentioning
confidence: 99%
“…Carnosic acid (1) and carnosol (8) are potent antioxidant (13), antiadipogenic (14), and anticancer agents (15,16), whereas several carnosic-acid-related diterpenes, such as 12-methoxy-carnosic acid (9) and pisiferic acid (7; Fig. 1A) have strong antiparasitic, antifungal, and antibacterial activities (17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential sites of other molecules intervention in the Wnt signaling pathway are shown schematically in Figure 1. LL3 may inhibit a similar axis to small molecule compounds PKF 115-854 and CGP049090, 25 in disrupting the b-catenin/TCF complex, or as carnosic acid inhibiting the interaction of b-catenin and Bcl -9, 21 or alternatively present a novel inhibitory axis between b-catenin and Pontin52. blot.…”
Section: Discussionmentioning
confidence: 99%
“…19 Mutations that over-activate the transcription of Wnt/b-catenin target genes are completely dependent on transcriptionally active nuclear b-catenin, hence disrupting the transcriptional activity of b-catenin is of great therapeutic interest. A number of previous studies have identified small molecule [20][21][22][23][24][25][26][27] and conventional antibody 28 inhibitors of the Wnt signaling pathway, shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%